2019
DOI: 10.1007/s40556-019-00194-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Calcium Levels in Preeclampsia Versus Normotensive Pregnant Women in a Tertiary Hospital: A Comparative Study

Abstract: The role of calcium supplementation in pregnancy to prevent preeclampsia is conflicting. The goal was to determine if there was significant difference between plasma calcium levels in women with preeclampsia and normotensive pregnant women. This was a cross-sectional study of 90 consecutive preeclamptic and 90 normotensive pregnant. Blood samples were taken from them and the plasma isolated from each was analyzed using colorimetric method for calcium and albumin employing calcium kit, albumin kit and spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…All of these investigations confirm our findings. In line with prior investigations, we additionally found that preeclamptic women had very low calcium levels [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…All of these investigations confirm our findings. In line with prior investigations, we additionally found that preeclamptic women had very low calcium levels [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, lower calcium level in umbilical-cord blood gas analysis as well as lower maternal serum calcium levels were found in the PE group compared with the control group. It is a known fact that calcium plays a crucial role in the fetal-placental-preeclampsia axis (23,24). Based on previous studies, patients with PE have low calcium levels and the benefits of prophylactic calcium replacement has been suggested (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…It is a known fact that calcium plays a crucial role in the fetal-placental-preeclampsia axis (23,24). Based on previous studies, patients with PE have low calcium levels and the benefits of prophylactic calcium replacement has been suggested (23,24). Sende et al similarly found that plasma calcium levels in PE group were significantly lower than in normotensive group (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings are in accordance to the results of previous studies. A study showed significantly reduced plasma calcium in preeclampsia than in the normal pregnancy (2.07 ± 0.318 mmol/L vs. 2.41 ± 0.224 mmol/L, P < 0.001), recommending calcium supplementation in pregnancy to decrease risk for preeclampsia [9]. Another study conducted on Bangladeshi women revealed that serum calcium levels were less in preeclampsia as compared to normal pregnancy (7.63±0.42 vs 8.12±0.94mg/dl, respectively) [10].…”
Section: Discussionmentioning
confidence: 99%